O62: INTRA-OPERATIVE ADJUNCTS IN MINIMALLY INVASIVE RADIO-GUIDED PARATHYROIDECTOMY AT A SPECIALIST ENDOCRINE SURGERY CENTRE. (27th April 2021) - Razzaq, Z; Majeed, M; Hanrahan, M; Cagney, D; O' Leary, DP; Redmond, HP
Abstract: Introduction: Primary Hyperparathyroidism (PH) is common cause of hypercalcaemia (0.3% of the population). Minimally invasive radio-guided parathyroidectomy (MIRP) has been made possible due to advancements in pre-operative imaging i.e. sestamibi scans allowing localisation of areas of parathyroid hyperactivity. Method: Due to the disagreement in the literature regarding which intra operative adjunct is best used in MIRP surgery to decrease recurrence, the rationale for this study is to examine and compare the performance of these adjuncts in consecutive patients i.e. 1. Intra operative PTH assay (IOPTHA) 2. Tc-99m radio-guidance using a gamma probe and the 20% rule 3. Frozen section analysis. Result: 45 MIRP procedures were carried out between 01/07/2018 and 30/10/2019. 77.8% were females; mean age was 62 years (range 30 - 79). Final pathology showed that in 43 of the cases parathyroid tissue was correctly removed; thyroid tissue was identified for the other 2 cases. 20% rule was positive in 43 out of the 45 cases and negative in 2 (sensitivity 100%, specificity 100%). A drop in IOPTHA greater than 50% was found in 41 out of the 45 cases but not in 4 (sensitivity 93.9%, specificity 100%). Frozen section was 100% concordant with final pathology (45/45). AUC analysis showed no significant difference in the performance of these tests (p = 0.15) but was around 1 for 20% rule and Frozen section. Conclusion: When radio-guidance and frozen sections are added to IOPTHA, the success rate of parathyroidectomy is markedly improved. Using them together will greatly reduce recurrent hyperparathyroidism. Take-home message: When radio-guidance and frozen sections are added to Intra-operative PTH assays in Minimally Invasive Radio-Guided Parathyroidectomy, the success rate of parathyroidectomy is markedly improved. Using them together as in our study will greatly reduce the incidence of recurrent hyperparathyroidism and thus recurrent surgery.